2002
DOI: 10.1021/ac010820+
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Understanding of an Absorption-Based Surface Plasmon Resonance Sensor Based on Kretchmann's Theory

Abstract: An optical-absorption-based surface plasmon resonance (SPR) sensor is proposed, and its theoretical aspects are discussed in terms of mathematical descriptions and numerical simulations of the SPR curve. The response theory of the absorption-based SPR sensing is based on the expansion of Kretchmann's SPR theory into the case in which optical absorption in the sensing layer is expressed by the Lorentz model. The numerical simulations were performed using a three-layer Fresnel equation of p-polarization. It was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
127
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 191 publications
(132 citation statements)
references
References 20 publications
4
127
0
1
Order By: Relevance
“…The SPR signal (reported as a function of particle surface coverage), varies for the resonance wavelengths of approximately 650 nm, 770 nm, and 920 nm, and is greatest at 770 nm. Modeling results using a simple absorptive Lorentz model [11,12] are shown to be in good agreement with the experimental data and are consistent with a red-shifted localized surface plasmon resonance (LSPR) absorption peak of 650 nm for the colloidal gold nanoparticles on planar gold. The results indicate that the resonance wavelength dependence of the colloidal gold nanoparticles on planar gold is a balance between this LSPR absorption peak in the visible range and the inherent sensitivity increase of SPR on planar gold in the NIR [13,14].…”
Section: Introductionsupporting
confidence: 70%
“…The SPR signal (reported as a function of particle surface coverage), varies for the resonance wavelengths of approximately 650 nm, 770 nm, and 920 nm, and is greatest at 770 nm. Modeling results using a simple absorptive Lorentz model [11,12] are shown to be in good agreement with the experimental data and are consistent with a red-shifted localized surface plasmon resonance (LSPR) absorption peak of 650 nm for the colloidal gold nanoparticles on planar gold. The results indicate that the resonance wavelength dependence of the colloidal gold nanoparticles on planar gold is a balance between this LSPR absorption peak in the visible range and the inherent sensitivity increase of SPR on planar gold in the NIR [13,14].…”
Section: Introductionsupporting
confidence: 70%
“…A simulation of the SPR curve change based on absorption changes of the sensing layer was performed in order to estimate the effect of the dye [17][18][19][20].…”
Section: Simulation Of Spr Curvementioning
confidence: 99%
“…Ion-optode membranes [14][15][16] were used as SPR-sensing layers. Based on the change of the color of a membrane-incorporated indicator dye, small molecules were successfully measured due to the change of the imaginary part of the surface refractive index [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…However, past studies have reported an enhancement in the sensitivity, if the antibody coating layer used for the detection of a specific antigen has an absorption band in the vicinity of the SPR resonance. [13][14][15][16][17] Moreover, Nakkach et al showed that the reflectivity variation can be enhanced by a factor of almost 160% by using appropriate dye molecules conjugated to the analyte (in this case DNA). 17 It is worth mentioning that in these studies strong interaction or coupling between the absorption bands of the antibody layer and the surface plasmon was not observed.…”
Section: Introductionmentioning
confidence: 99%
“…17 It is worth mentioning that in these studies strong interaction or coupling between the absorption bands of the antibody layer and the surface plasmon was not observed. 13,[15][16][17] On the other hand, several studies have dealt with strong coupling between surface plasmons and strongly absorbing dye molecule but these studies have not illustrated how the strong coupling phenomenon is favorable for sensing applications. [18][19][20][21][22][23] The phenomenon of strong coupling, which is typically characterized by an anti-crossing or avoided boundary crossing, is very well known and has been observed in different physical systems like cavity QED, [24][25][26][27][28][29] plasmonics, and photonics [30][31][32][33] and has been applied for the development of practical applications like plasmonic switches 34 and optical rulers.…”
Section: Introductionmentioning
confidence: 99%